The internal structure of fault zones : implications for mechanical and fluid-flow properties - Wibberley, C. A. J. (Geological Society special publication ;, 2008)
Faults are primary focuses of both fluid migration and deformation in the upper crust. The recognition that faults are typically heterogeneous zones of deformed material, not simple discrete fractures, has fundamental implications for the way geoscientists predict fluid migration in fault zones, as well as leading to new concepts in understanding seismic/aseismic strain accommodation. This book captures current research into understanding the complexities of fault-zone internal structure, and their control on mechanical and fluid-flow properties of the upper crust.